PENGARUH KEMUNGKINAN TERDETEKSINYA KECURANGAN, TEKNOLOGI DAN INFORMASI PERPAJAKAN, DAN KEPERCAYAAN PADA OTORITAS PEMERINTAH TERHADAP PENGGELAPAN PAJAK (Studi Empiris Pada Orang Pribadi Yang Terdaftar di Kantor Pelayanan Pajak Pratama Senapelan Pekanbaru) - Ulfa, Auliya; -, Desmiyawati; Lukman, Al Azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine the effect of the possibility of fraud detection, and information technology taxation and trust in government authorities against tax evasion in KPP Senapelan, the city of Pekanbaru.This research was carried out on individual taxpayers registered in KPP Senapelan, Pekanbaru. The number of respondents in this study were 100 respondents but were distributed to a total of 110 respondents because the return of questionnaires is still quite low . Data collection techniques in this study is in the form of a questionnaire , whereas the method of analysis used in this study was a multiple linear regression analysis with SPSS version 17. The results showed that the probability of detecting fraud, and tax information technology and trust in the government's authority to tax evasion. The coefficient of determination by the three variables in this study affect the dependent variable by 52%, while 48% are influenced by other variables that are not described in this study. Future studies are expected to use other variables outside the model of this research in order to enrich the knowledge, especially in the field of taxation.Keywords: Fraud , Information Technology, Trust Government, and Tax Evasion